2006
DOI: 10.1007/s10482-005-9034-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Streptomyces of high-mountainous ecosystems of Kyrgyzstan and its biotechnological potential

Abstract: The prevalence of actinomyces of Streptomyces class in various types of soils of Kyrghyzstan and the variety of its species have been investigated. It is shown that predominant members of Streptomyces complex are in the Cinereus section of Chromogenus series which are basically adapted to chestnut and black soil while species of the section Roseus of the Fuscus series are adapted in gray, brown, and chestnut soils. Their antibiotic and growth-stimulating effect and a great opportunity of use in biotechnologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…For example, strains of Streptomyces , Bacillus , Pseudomonas and Trichoderma were effective not only in helping plants to mobilize and acquire nutrients but also to control plant pathogens (Postma et al 2003 ; Khan et al 2004 ; Perner et al 2006 ; Borriss et al Borriss et al 2011 ; Gopalakrishnan et al 2011a , b ). Microorganisms with PGP and biocontrol potential were found at high incidence in compost, forest and pasture soils (Torsvik et al 2002 ; Tinatin and Nurzat 2006 ). PGP traits of actinomycetes have been reported on pea (Tokala et al 2002 ), bean (Nassar et al 2003 ), tomato (El-Tarabily 2008 ), wheat (Sadeghi et al 2012 ) and rice (Gopalakrishnan et al 2012a ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, strains of Streptomyces , Bacillus , Pseudomonas and Trichoderma were effective not only in helping plants to mobilize and acquire nutrients but also to control plant pathogens (Postma et al 2003 ; Khan et al 2004 ; Perner et al 2006 ; Borriss et al Borriss et al 2011 ; Gopalakrishnan et al 2011a , b ). Microorganisms with PGP and biocontrol potential were found at high incidence in compost, forest and pasture soils (Torsvik et al 2002 ; Tinatin and Nurzat 2006 ). PGP traits of actinomycetes have been reported on pea (Tokala et al 2002 ), bean (Nassar et al 2003 ), tomato (El-Tarabily 2008 ), wheat (Sadeghi et al 2012 ) and rice (Gopalakrishnan et al 2012a ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigation of new ecosystems for isolation of actinomycetes is crucial for the discovery of novel actinomycetes and subsequently for natural product-based drug discovery. Recently, several studies reported the investigation of different habitats for isolation of novel actinomycetes as rich sources of bioactive compounds (Magarvey et al 2004;Oskay et al 2004;You et al 2005;Badji et al 2006;Dolotkeldieva and Totubaeva 2006;Li and Liu 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Informations on their diversity could be improved by improvement in isolation methods. Also, unexplored ecological niche or underexploited habitats such as mountainous ecosystems (Dolotkeldieva and Totubaeva 2006) and the rhizosphere and endosphere of not yet studied plants could be pursued as sources of new Actinobacteria. Particularly, indigenous plants might be a rich source of novel actinomycetes species (Bouizgarne et al 2009;Kirby and Meyers 2010).…”
Section: Resultsmentioning
confidence: 99%